Therapeutic exercise in cancer cachexia: exploring approaches and outcomes - Maddocks, Matthew (2010)
Cachexia is common in patients with incurable cancer, particularly of the lung and upper-gastrointestinal tract, and impacts adversely on treatment options, morbidity, quality of life and survival. Current management of cancer cachexia is inadequate and progress is required. This thesis explores the use of exercise as a proactive supportive therapy with a focus on maintaining physical function.